Quality management in hospitality : best practice in action - Lockwood, Andrew; Baker, Michael; Ghillyer, Andrew (London : Cassell, 1996)
This book is about: Hospitality and Quality; A systematic approach to quality; Alpha flight services; Country club hotel group; English lakes hotels; ....
Keywords: Management; Hospitality industry; Hospitality industry -- Great Britain -- Management; Total quality management -- Great Britain; Tourism -- Management; Quality assurance -- Great Britain